Smart modeling of soil-foundation interaction using coupled mechanisms: a numerical framework for liquefaction risk mitigation - Kumari, Sunita; Ghani, Sufyan; Kumar, Amrendra (Frontiers in Built Environment, 2024)
This study investigates the impact of nearby structures on the cyclic settlement mechanisms of shallow foundations in liquefiable soils using a numerical model based on Biot’s porous media theory. The model predicts excess pore water pressure and settlement by coupling equilibrium and continuity equations, solved using an implicit time integration scheme. Soil nonlinearity under cyclic loading is represented using generalized plasticity, boundary surfaces, and non-associated models. Three scenarios are simulated to study the effect of spacing between light and heavy foundations and variation in acceleration intensity. Results show that as spacing between foundations increases, lateral displacement and settlement decrease. Excess pore water pressure generation also decreases with increased foundation spacing. Soil just below the foundation exhibits maximum settlement, decreasing with depth. When input acceleration increases from 0.1 g to 0.15 g and 0.2 g, settlement increases by 40%–55% and 90%–110% respectively for both light and heavy foundations, regardless of spacing. Excess pore water pressure also increases sharply with higher acceleration intensity. The findings highlight the importance of considering foundation-soil-foundation interaction effects in liquefaction-prone urban settings and provide insights for designing resilient shallow foundations. The advanced numerical modeling approach offers engineers a more informed way to mitigate liquefaction risk and build safer, more durable structures in earthquake-prone areas.